Post-traumatic stress disorders and its relationship to social participation among a sample of refugee adult torture victims in Jordan - Al-Emoush, Maram Farhan; Banat, Sohaila Mahmoud (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the relationship between post-traumatic stress disorder and social participation among a sample of adult refugee victims of torture in Jordan The study sample consisted of (126) refugees, beneficiaries from Institute for Family Health in all locations. This study adopted the descriptive correlative method, the scales of The post-traumatic stress disorder, and the social participation scale were developed for the purpose of this study. The results indicated that the level of the (PSTD) among study sample was high, and level of the social participation were low, and the results indicated that there are statistically significant differences between male and female in (PTSD), and that the (PTSD) was higher for refugees males. The results also indicated that there were statistically significant differences due to nationality in favor of Sudanese and Yemeni nationalities. The results indicated that there were no statistically significant differences in (PTSD) attributed to the effect of social status, the results indicated that there were statistically significant differences between male and female in social participation, in favor of female refugees. The results indicated that there were no statistically significant differences in social participation due to the effect of social status, and the results also showed that there were statistically significant differences due to nationality in favor of Syrian nationalities. The results also revealed that there was a statistically significant inverse relationship between the level of PTSD and the social participation of adult survivors of torture. The study recommended the need to continue providing psychological services to reduce the severity of PTSD, and to enhance social participation among refugees.
Keywords: post-traumatic stress disorder; social participation; victims of torture